Structural Evaluation of the Effect of Bone Quality on the Mechanical Interaction between Dental Implants and Bone - Nazanin Karami; Mehdi Razeghi (Shock and Vibration)
When one or more teeth are lost for any reason such as accident, caries, and gum disease, they should be replaced with dentures. Researchers discovered that titanium successfully bonds to bone because of the development of osteoblasts on its rough surface. However, the success of dental implants depends on biological, mechanical, and chemical factors. Each of these factors is itself a function of different parameters that, any changes in these factors affect the mechanism of transfering from the prosthesis to the implant and from implant to bone. The role determinant in the success of implant therapy is the function of the geometry and mechanical properties of the implant, jaw and bone-implant joint. Now, due to the increasing use of dental implants, various companies are constantly launching their new products and, as a result, express many benefits of these products, which in most cases are based on their claims. It is not a long-term study, and therefore it is not possible to make an accurate judgment on the designs, macroscopic and microscopic properties, and benefits offered, due to the lack of accurate and practical comparisons between systems. It will not be possible to prove the effectiveness of each of them. Therefore, understanding the design method and its philosophy, along with familiarity with the types of systems available in the market, is a determining factor in the clinical success of dental implant treatment. The presence of threads prevents overload on the surface of the cortical bone and reduces this load by up to 36%. Reducing the thread pitch contributes to the stability of the implant, and increasing the depth of the thread stabilizes patients with poor bone quality. The behavior of the bone and its relation to the implant with regard to applied loads with a maximum inclination angle of 15° have been evaluated by evaluating the tension in the bony areas of the cortex and trabecular bone.